Sex differences in atrial fibrillation: patient-reported outcomes and the persistent toll on women - Raisa L. Silva; Emily N. Guhl; Andrew D. Althouse; Brandon Herbert; Michael Sharbaugh; Utibe R. Essien; Leslie R.M. Hausmann; Jared W. Magnani (Elsevier, 2021)
Background: Women have worse patient-reported outcomes in atrial fibrillation (AF) than men, but the reasons remain poorly understood. We investigated how comorbid conditions, treatment, social factors, and their modification by sex would attenuate sex-specific differences in patient-reported outcomes in AF. Methods: In a cohort with prevalent AF we measured patient-reported outcomes with the Short-Form-12 (SF-12, an 8-domain quality of life measure), and the AF Effect on QualiTy of Life (AFEQT), an instrument specific to AF, both with range 0-100 and higher scores indicating superior outcomes. We examined sex-specific differences in patient-reported outcomes in multivariable-adjusted regression analyses incorporating demographics, comorbid conditions, treatment, social factors, and their sex-based modification. Results: In 339 individuals (age 72±10, 45% women), women (vs. men) reported worse physical functioning on the SF-12 (49.7±39.0 versus 65.0±34.0), social functioning (69.8±31.8 versus 79.7±25.8), and mental health (67.4±20.2 versus 75.0±18.6). These differences were attenuated with adjustment for comorbid conditions and depression. Women had worse composite AFEQT scores (73.8±18.4 versus 78.5±16.6) and symptoms and treatment scores than men with differences remaining significant after multivariable adjustment. There were not significant interactions by sex and the array of covariates when examining differences in patient-reported outcomes between women and men. Conclusions: We identified sex-specific differences in patient-reported outcomes assessed with general and AF-specific measures. Compared to men, women with AF reported worse overall health-related quality of life, even after consideration of both relevant covariates and their modification by sex. Our research indicates the importance of consideration of sex-based inequities when evaluating patient-reported outcomes in AF.